2017
DOI: 10.3892/mmr.2017.8164
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of COUP‑TFII suppresses proliferation and metastasis of human gastric cancer cells

Abstract: The abnormal expression of the chicken ovalbumin upstream promoter transcription factor 2 (COUP-TFII) is associated with numerous forms of cancer, including gastric, prostate, colon and lung cancer. However, previous studies investigating the association between COUP-TFII expression and the occurrence, recurrence, invasion and metastasis of gastric cancer are limited in number. In the present study, it was revealed that the expression of COUP-TFII is significantly reduced in gastric carcinoma tissues compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…The ability to direct angiogenesis is paralleled by its role in mesenchymal cell differentiation and point to a role of the NR in regulating the cells micro-environment with evident implications for several pathologies [45,54,74,95,117,128,132,146]. Indeed, the NR expression (or the absence thereof) is associated with the unfavorable progression of malignancies in several organs [157,163,165,167,173,181]; besides, COUP-TFII is linked to pathologies considered cancer risk factors, such as diabetes or cirrhosis [54,64].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ability to direct angiogenesis is paralleled by its role in mesenchymal cell differentiation and point to a role of the NR in regulating the cells micro-environment with evident implications for several pathologies [45,54,74,95,117,128,132,146]. Indeed, the NR expression (or the absence thereof) is associated with the unfavorable progression of malignancies in several organs [157,163,165,167,173,181]; besides, COUP-TFII is linked to pathologies considered cancer risk factors, such as diabetes or cirrhosis [54,64].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this finding, COUP-TFII is more expressed in normal gastric mucosa cells (GES-1) compared with gastric cancer cells and gastric carcinoma tissues. Moreover, GES-1 cells with COUP-TFII knocked down have increased proliferation and invasiveness while COUP-TFII overexpression in xenograft tumor models reduces the tumor burden [165]. Finally, confronting the pathological data from 80 gastric cancer patients obtained from the Oncomine database, Ding et al demonstrated that high expression of COUP-TFII correlates with increased survival [165], in stark contrast with the results of Feng et al [166].…”
Section: The Gastrointestinal Cancers: Mostly An Oncogenementioning
confidence: 99%
See 2 more Smart Citations
“…Ding et al 48 showed that COUP-TFII expression was reduced in gastric carcinoma tissues and gastric carcinoma cell lines compared with normal gastric mucosa tissues and normal gastric mucosa cells (GES-1), respectively. They also demonstrated that overexpressing COUP-TFII inhibited the proliferation, migration, and invasion of gastric cancer cells in vitro and inhibited the growth and hepatic metastasis of gastric cancer in vivo; however, they did not provide the underlying mechanisms for these activities of COUP-TFII in gastric cancer.…”
Section: Tumor Suppressive Effect Of Coup-tfii In Gastric Cancermentioning
confidence: 99%